Social Education Dimensions and Components and Their Educational Implications from the Perspective of Gottfried Wilhelm Leibniz - Hassanniai Damouchali , Robabeh; Fallah, Vahid; Salimi , Ladan (Assessment and Practice in Educational Sciences, 2025)
The present study aimed to identify the dimensions and components of social education from the perspective of Gottfried Wilhelm Leibniz and to analyze its educational implications within a comparative framework emphasizing rationality, justice, and the common good. This study employed a qualitative directed content analysis approach grounded in philosophical-educational inquiry. Data were collected through documentary analysis of Leibniz’s principal philosophical works, including Monadology, Discourse on Metaphysics, Theodicy, and selected philosophical correspondences. Textual units related to ontology, anthropology, epistemology, ethics, and social order were extracted and analyzed using MAXQDA software through open, axial, and selective coding procedures. The analysis process resulted in the extraction of 51 primary codes and several organizing and overarching themes concerning metaphysical foundations, rational selfhood, justice, collective harmony, and social responsibility. To ensure trustworthiness, the study applied peer review, repeated recoding, reflexive analysis, and Holsti reliability testing. The findings revealed that Leibniz’s philosophical system provides a coherent framework for theorizing social education despite its highly metaphysical structure. Five overarching dimensions of social education were identified: metaphysical foundations of social education, anthropological foundations, epistemological foundations, ethical-social foundations, and educational aims and implications. The results indicated that the individual, as a self-active monad harmonized with the whole, constitutes the basis of social order. Social education in Leibniz’s thought is directed toward the awakening of reason, the transition from sensory perception to reflective rational awareness, and the cultivation of justice as “wise benevolence.” The analysis further demonstrated that social harmony emerges not through external coercion but through the internal rational coordination of autonomous individuals. Moreover, justice was conceptualized as a socially preservative moral duty oriented toward the common good and extending responsibility toward future generations. Comparative interpretation also showed substantial convergence between Leibnizian rational ethics and the ethical-social teachings of Nahj al-Balagha regarding justice, moral responsibility, collective welfare, and the integration of reason and ethics in social life. The study concluded that Leibniz’s philosophy possesses significant potential for reconstructing a comprehensive model of contemporary social education grounded in rationality, ethical responsibility, and collective harmony. In this framework, education is not merely a mechanism for social adaptation but a transformative process aimed at cultivating rational self-awareness, social responsibility, and benevolent justice. The integration of Leibnizian rationalism with the justice-oriented ethical framework of Nahj al-Balagha can contribute to the development of a balanced educational paradigm that simultaneously promotes individual perfection and social cohesion while responding to contemporary moral and social crises.